2017
DOI: 10.56178/eh.v32i2.508
|View full text |Cite
|
Sign up to set email alerts
|

Variaciones anuales en la abundancia y en la distribución espacial del Flamenco Austral (Phoenicopterus chilensis) y la Parina Grande (Phoenicoparrus andinus) en el Sitio Ramsar Laguna Melincué, Argentina

Abstract: Durante 1999–2016 se realizaron conteos invernales de Flamenco Austral (Phoenicopterus chilensis) y Parina Grande (Phoenicoparrus andinus) en distintos sectores de la laguna Melincué y se registraron las variaciones en el nivel del agua y su salinidad. Además, se registraron las posiciones de individuos de Parina Grande equipados con transmisores. La cota fluctuó entre 86.1–82.3 msnm. En 2005 se empezó a bombear agua y la conductividad disminuyó marcadamente. La conductividad estuvo asociada positivamente con … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…On the other hand, the Chilean flamingo is a selective predator that feeds on larger macrophytes and zooplankton, and is generally found in deep lakes, while the Andean flamingo is non-selective and is found in shallow lakes (Battauz et al 2013;Caziani and Derlindati 2000). Additionally, it has been observed that the abundance of flamingos increases when the water level decreases (Romano et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the Chilean flamingo is a selective predator that feeds on larger macrophytes and zooplankton, and is generally found in deep lakes, while the Andean flamingo is non-selective and is found in shallow lakes (Battauz et al 2013;Caziani and Derlindati 2000). Additionally, it has been observed that the abundance of flamingos increases when the water level decreases (Romano et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Flamingos (Phoenicoptaridae) are gregarious birds that inhabit shallow, brackish water environments (Barison et al 2014), ranging from sea level to approximately 4 500 meters above sea level (Romano et al 2017). Currently, there are four species of flamingos in South America: Phoenicopterus ruber (American flamingo), P. chilensis (Chilean flamingo), Phoenicoparrus jamesi (James's flamingo), and Phoenicoparrus andinus (Andean flamingo) (SACC), and three of them (P. jamesi, P. andinus, and P. chilensis) have been recorded in Peru (Rodríguez 2005;Caziani et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Tres especies de flamencos Phoenicoparrus andinus Philippi, 1854 (flamenco andino), Phoenicoparrus jamesi Sclater, 1886 (flamenco de james) y Phoenicopterus chilensis Molina, 1782 (flamenco chileno o austral) son las representativas de los salares y lagunas de los Andes centrales de Sudamérica, distribuyéndose entre los países de Argentina, Bolivia, Chile y Perú (Suárez, 2020;Ortiz et al, 2023). Son aves gregarias que nidifican en colonias y pueden viajar grandes distancias entre sitios de alimentación y cría (Romano et al, 2017). El flamenco chileno es el más común y de mayor distribución en Bolivia, que puede ser observado en bandadas de miles en lagunas altoandinas y en menor número en lagos y lagunas de agua dulce y bofedales (Herzog et al, 2017).…”
Section: Introductionunclassified
“…Estos movimientos no son todos los años, ni a los mismos lugares, ni en la misma temporada; ocurren ocasionalmente y en algunos casos están asociados a cambios climáticos a escala regional o local, por ejemplo sequías severas (Caziani & Derlindati, 2000) o fuertes tormentas (Guilherme et al, 2005). Entendiéndose, de esta manera, que sus movimientos están asociados principalmente a fluctuaciones rápidas de agua en sus hábitats (Romano et al, 2017).…”
Section: Introductionunclassified